Exposure of workers to a mixture of toluene and xylenes. II. Effects. Issue 1 (January 1994) - Chen, Z; Liu, S J; Cai, S X; Yao, Y M; Yin, H; Ukai, H; Uchida, Y; Nakatsuka, H; Watanabe, T; Ikeda, M
Abstract : The health effects of exposure to a mixture of toluene and xylene isomers was studied on the fourth or fifth days of a working week in factories in China. The study population comprised 233 subjects (122 men and 111 women), who were exposed to the time weighted geometric mean (maximum) concentrations of toluene (3 (203) ppm) and xylenes (4 (103) ppm). For comparison, 241 non-exposed controls (116 men and 125 women) were recruited from the same regions. The prevalence of some subjective symptoms significantly increased in the exposed population, and the symptom profiles were similar to those found after exposure to toluene or xylenes alone. Haematology and serum biochemistry did not show notable changes. It seems reasonable to conclude that the effects of the toxicities of toluene and xylenes in combination are additive.